“Tukar Gawan” Tradisi Jawa Kirim Doa Jumat Legi di Desa Ngebruk - Aulia Novianty Ardini; Ali Badar (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
The tradition of exchanging gawan is one of the original cultures of the Ngebruk village community, which is still carried out today as a form of respect for ancestors.